Molecular mechanism of Epimedium in the treatment of vascular dementia based on network pharmacology and molecular docking - Xie, Chenchen; Tang, Hao; Liu, Gang; Li, Changqing (Frontiers in Aging Neuroscience, 2022)
Backgroud: Vascular dementia is the second most common cause of dementia after Alzheimer’s disease, accounting for an estimated 15% of cases. Recently, Epimedium has attracted great attention for its potential neuroprotective benefit. However, the direct role and mechanism of Epimedium on vascular dementia still lack systematic research. To systematically explore the possible pharmacological mechanism of Epimedium for the treatment of vascular dementia, network pharmacology, molecular docking, combined with experiment validation were conducted. Methods: The bioactive compounds and targets of Epimedium were obtained from the TCMSP database. The potential targets of vascular dementia were identified from the DrugBank, OMIM, Genecards, Therapeutic Target Database, and DisGeNET databases. GO and KEGG pathway analyses were performed. Molecular docking was applied to validate the interaction between active components and hub targets. The bilateral common carotid artery occlusion (BCCAO) method was used for construction of a vascular dementia model in mice. The effects of Epimedium on learning and memory ability were examined by behavioral tests. The mechanisms of the cerebral protective effects of Epimedium were evaluated by WB, RT-PCR, and immunofluorescence. Results: A total of 23 Epimedium active ingredients, and 71 intersecting targets of Epimedium against vascular dementia were obtained. The top five hub targets AKT1, TNF, IL1β, IL6, and MMP9 were identified, and molecular docking showed good binding. GO enrichment showed a total of 602 enrichment results, with 458 (80.56%) key targets mainly focused on biological processes (BP). The response to hypoxia, positive regulation of nitric oxide biosynthetic process, aging, inflammatory response, cellular response to lipopolysaccharide, negative regulation of apoptotic process were well ranked. KEGG pathway enrichment analysis identified the TNF signaling pathway as an important pathway, with the MAPK/extracellular signal-regulated kinase (ERK) and NF-κB signaling pathways as the key pathways involved. Consistently, in vivo experiments showed that Epimedium treatment improved learning and memory functions in mice with vascular dementia. In addition, Epimedium attenuated the activation of microglia and astrocytes in the hippocampal region after BCCAO. RT-qPCR and Western blot analysis showed that Epimedium not only affected the expression of AKT, TNF, IL1β, IL6, and MMP9, but also suppressed the TNF signaling pathway. Conclusion: Epimedium may exert a protective effect against vascular dementia through the alleviation of oxidative stress, neuroinflammation, BBB dysfunction, apoptosis through TNF signaling pathway. This study explored the mechanism of Epimedium on vascular dementia systematically through network pharmacological and in vivo experiment approach, which provides insight into the treatment of vascular dementia.